An Overview of Psychological Well-Being in First-Year Students of Faculty of Nursing - Nugraha, Revi Merliani; Rafiyah, Imas; Yulianita, Henny (Universitas Pendidikan Indonesia, 2024)
Introduction: First year students are often faced with various challenges that have an impact on their psychological well-being. So far, the psychological well-being of first-year nursing students is not clearly known. Good psychological well-being helps first-year nursing students cope with academic demands. Objective: This study aimed to describe the psychological well-being of first-year students at the Faculty of Nursing, Padjadjaran University. Methods: This study used a quantitative descriptive method. The population of this study were all first-year active students, namely the 2022 batch of the Faculty of Nursing, Padjadjaran University, Bachelor Study Program (N=234). The sampling technique in this study is total sampling. This study used the Ryff’s Psychological Well-Being Scale Instrument with 48 statement items that have been adapted to Indonesian language and culture with a validity index of 0.304 - 0.580 and a cronbach alpha coefficient of 0.912. Data analysis in this study used univariate analysis. Results: The results showed that 6.4% of students had high psychological well-being, 87.6% of students had moderate psychological well-being, and 6.0% of students had low psychological well-being. Almost all first-year students of the Faculty of Nursing, Padjadjaran University have psychological well-being in the moderate category. Conclusion: For the faculty, it is hoped that they can make efforts to monitor the psychological well-being of students by promoting available counseling service facilities so that students can find out and take advantage of existing facilities, and further research is expected to be able to examine other factors that can affect psychological well-being which were not discussed in this study.